Reformulasi Perkap No. 8 Tahun 2011 tentang Pengamanan Eksekusi Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi Nomor : 18/PUU-XVII/2019 - Syairulan A. Radjak; Ahmad, Ibrahim; Moonti, Roy Marthen (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Guarantee fiduciary guarantees play an important role in economic financing in Indonesia. However, implementation of fiduciary guarantee execution often leads to legal conflicts, especially the abuse of executorial power by creditors. Court Decision Constitutional Court Decision Number 18/PUU-XVII/2019 changes the execution mechanism to better protect the rights of debtors and emphasize the principle of justice. protect the rights of debtors and emphasize the principle of justice. This raises the need to reformulate Perkap No. 8/2011 to be relevant to the changes.changes. Research This research uses a normative method that analyzes the relevant laws and regulations related laws and regulations, the principles of justice, and their compatibility with social dynamics. The focus is to review the relevance and weaknesses of Perkap No. 8/2011 after the Constitutional Court Decision. The Constitutional Court's ruling limits unilateral execution and requires an acknowledgment of default or a court decision before execution. default or court decision before execution is carried out. This increases the protection of debtors' rights, but also adds procedural burdens for creditors. for creditors. The reformulation of Perkap No. 8/2011 is necessary to ensure that execution is more fair and lawful. The reformulation should include mechanisms that prioritize legality, protection of debtor rights, and oversight of abuse. monitoring against abuse. Synergy between the court, the police, and related parties need to be strengthened to create a balanced and transparent legal ecosystem and transparent.